Mate Choice Behavior of Female Field Crickets Is Not Affected by Exposure to Heterospecific Calling Songs. Issue 3 (9th April 2020) - Kuriwada, Takashi; Kawasaki, Rintaro; Kuwano, Akifumi; Reddy, Gadi V P
Abstract: Many animals produce acoustic signals to mark territories and attract mates. When different species produce acoustic signals simultaneously, the signals create a noisy environment, with potential acoustic interference between species. Theoretical studies suggest that such reproductive interference may have strong effects on species interaction. For example, the inferior resource competitor can survive if its disadvantage is counterbalanced by superiority in reproductive interference. Two field cricket species, Teleogryllus occipitalis (Audinet-Serville) (Orthoptera: Gryllidae) and Loxoblemmus equestris Saussure (Orthoptera: Gryllidae), cooccur in the same habitat. A previous study has shown that L. equestris is an inferior species to T. occipitalis in terms of resource competition. Therefore, we predicted that mate location and choice behavior of female T. occipitalis would be negatively affected by the acoustic signals of L. equestris and tested this with a series of playback experiments. The mate choice behavior of female T. occipitalis was not significantly affected by the calling song of L. equestris . Our results suggest that the acoustic interference does not explain the cooccurrence of the two species in the same habitat.